(In)adequate Housing and Health and Well-Being Impacts for Street-Connected Young People in Western Kenya: A Qualitative Study - Embleton, Lonnie; Chory, Ashley; Genberg, Becky; Kirwa, Sheila; Kiptui, Reuben (International Journal on Homelessness, 2026)
Adequate housing is a human right. In Kenya, there has been limited research on adequate housing for street-connected young people. Yet, young people’s street-involvement in this context has been linked to human immunodeficiency virus (HIV) acquisition, poor HIV treatment outcomes, adverse sexual and reproductive health outcomes, poor mental health, substance use, and physical and sexual violence. Considering the limited research on housing for street-connected young people in Kenya, we sought to explore barriers to and facilitators of adequate housing for this population in western Kenya and illuminate how homelessness and (in)adequate housing impacts street-connected young women’s health and well-being. From June to August 2023, we conducted key informant interviews with community interest holders, as well as street-connected young women participating in a direct cash transfer pilot project. Our analysis explores the significance of adequate housing and contrasts the views of community interest holders and street-connected young women about the elements of adequate housing. The findings identify complex and interrelated barriers to adequate housing, such as stigmatization, financial resources, education, and local policies, and illuminates how inadequate housing influences adverse health outcomes such as HIV acquisition and treatment, violence, and unintended pregnancy. To secure adequate housing, participants explained the reciprocal relationships between livelihoods, savings, food security, and the ability to pay rent. In turn, young people discussed that adequate housing would support them to transition from the streets, provide hope, dignity, stability, and security, and improve HIV-related and other health outcomes. Overall, our analysis demonstrates the critical need to intervene to reduce homelessness and improve access to adequate housing for street-connected young people to reduce the harms associated with street-involvement and to contribute to ending the HIV epidemic.